Assessment of Development Results - Malaysia - Programme des Nations Unies pour le Développement (United Nations, 2015)
The Assessment of Development Results (ADR) for Malaysia was conducted by the Independent Evaluation Office of the United Nations Development Programme (UNDP) in 2014. The ADR examines the Malaysia country programme over the 2008-2014 and covered the previous country programme 2008-2012, and as much as possible of the on-going country programme 2013-2015.This is the first ADR conducted in Malaysia. It was carried out in close collaboration with the Government of Malaysia through the Economic Planning Unit (EPU) of the Prime Minister’s Department, various other national stakeholders, the UNDP Malaysia Country Office and the Regional Bureau for Asia and the Pacific.